Lukas 18 : 35–43 Sebagai Landasan Misi Gereja dalam Melaksanakan Pemberdayaan Kaum Disabilitas - Staryan Yohanis Yohanes Najoan; Andheralvi Isaiah Lontoh (Predica Verbum: Jurnal Teologi dan Misi, 2025)
The Church's mission is to protect and heal everyone holistically. Interpreting this vocation, the existential church must not limit its approaches in the world. This article was prepared as a form of concern for those who have not felt real acceptance from the church due to different physical conditions. The Church must base its mission on the ethical-theological values that this article draws from a passage from Luke 18:35-43. In the work of preparing this article, qualitative research, literature study approach and also narrative hermeneutic study are used to see the full text used. The research uncovered a heartbreaking reality when churches were found to be less concerned with issues related to the needs of people with disabilities and unconsciously turned a blind eye to the church's behavior of trying to separate itself from the interests of people with disabilities. This is contrary to what the text of Luke 18:35-43 offers regarding friendliness and concern for the disabled. The deciphering of the narrative of this text generates a new idea that can help the church to act more inclusively, liberatively, and transformatively in a way that is not limited to acceptance but goes beyond empowerment that brings holistic healing.